Percutaneous renal mass biopsy: historical perspective, current status, and future considerations. Issue 4 (3rd April 2019) - Cotta, Brittney H.; Meagher, Margaret F.; Bradshaw, Aaron; Ryan, Stephen T.; Rivera-Sanfeliz, Gerant; Derweesh, Ithaar H.
ABSTRACT: Introduction : Percutaneous renal mass biopsy has evolved over the last decade with improvements on previous pitfalls including low tissue yield, high non-diagnostic rates, and complications. As understanding of tumor biology and natural history of renal cortical neoplasms has improved, percutaneous renal mass biopsy is poised to have an expanding role in an area characterized by individualized management and refined risk stratification. Areas covered : This review summarizes the evolution of renal mass biopsy to its current state with respect to outcomes, indications, and clinical guidelines. Expert opinion : With improved understanding of differential biological potential of renal cortical neoplasms combined with technical improvements in diagnostic yield and accuracy, utilization of renal mass biopsy is becoming an important adjunct to patient care in a broad range of clinical scenarios, including active surveillance, thermal ablation, and use of primary systemic therapy in localized and advanced settings.